Alternative Energy : political, economic, and social feasibility - Simon, Christopher A., 1968- (Lanham: Rowman & Littlefield, 2020)
"Discusses the basic technical aspects of major renewable energy systems and technological developments and the impact of politics on energy policy using contemporary theories of public policy, as well as discussing the evolution of the social feasibility of renewable energy"--
Includes bibliographical references and index.
Keywords: Renewable energy sources -- Government policy -- United States; Energy policy -- United States; Renewable energy sources